Dettera: Ilusão e Verdade - Sobre a (im)propriedade em Alguns Narradores de Graciliano Ramos - Facioli, Valentin (Revista do Instituto de Estudos Brasileiros, 1993)
Follower ot hte realisitie and new-realistic aesthetics Graciliano Ramos had an anti-modernist posture and a theorical reflexion fairly simple. The deliberate narrators relate conflicting with the so-called necessities by the democratic conviviality of the modern burgeois propery. Such narrators provided the reader seduction strategies that turned out contradictory. The realistic look of Graciliano Ramos searched with this narrator differentiae truth and illusion in the process of economical and social modernization of the country.